1997
DOI: 10.1097/00000658-199707000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m-HMPAO White Blood Cell Scan for Diagnosis of Acute Appendicitis in Patients With Equivocal Clinical Presentation

Abstract: ObjectiveThe authors' goal was to evaluate the accuracy of Technetium 99m-HMPAO-labeled leukocyte imaging for screening patients with atypically presenting appendicitis and to determine how availability of this test affected practice patterns of surgeons at the authors' medical center. Summary Background DataAppendicitis can be difficult to diagnose and in equivocal cases usually requires inpatient observation. The delay may increase morbidity and costs. A test that rules out acute appendicitis could be cost e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…Strategies to improve the early diagnostic accuracy and riskstratification of patients presenting with acute abdominal pain have included clinical scoring methods [5,6], blood and urinary markers [7,8], ultrasound and CT imaging [5,[9][10][11][12][13][14] and minimally-invasive surgery [15]. The complexity of presentation of acute abdominal pain has not produced a simple score that is clinically useful.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to improve the early diagnostic accuracy and riskstratification of patients presenting with acute abdominal pain have included clinical scoring methods [5,6], blood and urinary markers [7,8], ultrasound and CT imaging [5,[9][10][11][12][13][14] and minimally-invasive surgery [15]. The complexity of presentation of acute abdominal pain has not produced a simple score that is clinically useful.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, studies of white blood cell scan, ultrasonography (US), and computed tomographic (CT) scan have suggested that these diagnostic imaging modalities may improve the diagnostic accuracy for acute appendicitis. [8][9][10][11] On the other hand, there were also concerns about the appropriateness and accuracy of these modalities without a surgical evaluation. 10,11 At our institution, history and physical examination, followed by pathologic confirmation after appendectomy, typically diagnose acute appendicitis.…”
mentioning
confidence: 99%
“…[10][11][12][13] The primary disadvantages of radiolabeled WBC imaging include a lengthy preparation time of 2 hours and sometimes longer if an off site radiopharmacy is used, the requirement of ex vivo white blood cell radiolabeling, the potential for external blood contamination and misadministration, personnel exposure to blood borne infection such as hepatitis and HIV, and the relatively high cost and technical demand of the procedure. Because of these disadvantages, very few medical centers are capable of using radiolabeled WBC imaging for the diagnosis of appendicitis.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 This test was found to have high sensitivity (98%) and negative predictive value (98%), though a positive scan was not highly specific for appendicitis. Nonetheless, surgeons who received a positive scan result generally had a heightened degree of suspicion and treated the patient accordingly.…”
Section: Discussionmentioning
confidence: 99%